2018
DOI: 10.1002/pssb.201700570
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Film Thickness on Photoelectrochemical Performance of SnO2 Prepared via AACVD

Abstract: Tin (IV) oxide (SnO 2 ) is a stable semiconductor and has been used in a wide range of applications. In this work, aerosol-assisted chemical vapor deposition (AACVD) technique is employed to deposit SnO 2 thin film with different layer thicknesses by controlling the deposition time. The morphological and optical properties of SnO 2 layer are investigated thoroughly to understand the relationship between the deposition time and SnO 2 performance in photoelectrochemical cells. The bandgap energy of all SnO 2 thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 41 publications
1
10
0
Order By: Relevance
“…This stems from the larger distance charge has to travel through the NiO film before being collected on the external circuit. Such a condition intensifies the charge recombination rate within the device . The J sc obtained from the current–voltage curves are confirmed and supported by the IPCE measurement, and the calculated short‐circuit current densities are 9.47, 15.69, 18.08, and 12.81 mA cm −2 for devices using NiO deposited for 30, 45, 60, and 75 min.…”
Section: Resultssupporting
confidence: 67%
“…This stems from the larger distance charge has to travel through the NiO film before being collected on the external circuit. Such a condition intensifies the charge recombination rate within the device . The J sc obtained from the current–voltage curves are confirmed and supported by the IPCE measurement, and the calculated short‐circuit current densities are 9.47, 15.69, 18.08, and 12.81 mA cm −2 for devices using NiO deposited for 30, 45, 60, and 75 min.…”
Section: Resultssupporting
confidence: 67%
“…01-074-4894) for BiVO 4 . The peak intensities of (121), (040), (051), (042), and (161) support that g-C 3 N 4 @BiVO 4 has better crystallized structures. , It can be concluded that γ radiation has a negligible effect on the crystalline structure of g-C 3 N 4 @BiVO 4 , which is due to the close packing of atoms.…”
Section: Resultsmentioning
confidence: 74%
“…Several processing parameters are involved in the spinning process such as solution viscosity, solution concentration, spin time, and spin speed . This technique is necessary that forms a uniform layer to prevent a pinhole and large surface area from absorbing more light. ,, The existence of the elements of C and N in the samples was supported by EDX analysis as shown in Figure c. It can be observed no other impurity peak was detected, except the peak of Sn (probably attributed to the FTO).…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…The significantly higher band gap of our as‐synthesized pcaSS, compared with other metal oxides or nitrides, enabled the achievement of a high transmittance of above 80% down to wavelength of 250 nm. In fact, the substitution of metal (M) site in the perovskite structure of (M)SnO 3 with another element with larger atomic radius such as Barium culminated in the formation of the lower band gap BaSnO 3 (≈3.4 eV), that is unsuitable for ultraviolet TCE.…”
Section: Performance Comparison Of Different Tcesmentioning
confidence: 99%